The Perplexing Bilateral Relations between Two Koreas: Finding Peace in Korean Reunification Through Critical Theory's Perspective - Rahmawati, Dea (Insignia: Journal of International Relations, 2023)
Despite being formerly homogeneous in terms of history, culture, language, and nation, the separation of the Korean people has led to significant contrasts in political, economic, and cultural aspects between South Korea and North Korea. Conflict resulting from these differences eventually leads to war. However, since World War II, the two Koreas have been seeking reunification in three different ways: "reunification through war," "reunification through revolution," and "peaceful reunification." These Three Concepts of Korean Reunification was driven by the distortion of the term peace. This research employed a case study method to analyze a specific historical event to gain a comprehensive understanding of peace related to the three different concepts of Korean Reunification. Peace is essential for the realization of the reunification of separated nations. The Korean reunification program is affected by the research finding that given their common ethnicity, culture, familial ties, economic complementarity, international diplomacy, humanitarian concerns, and nuclear disarmament, the reunification process between North and South Korea has the possibility for peaceful reconciliation. However, a distorted understanding of peace has created challenges in Korea Reunificationwhere peace was built on mutual distrust and fear, making achieving a positive and sustainable peace exceedingly difficult, and meaningful reunification has yet to occur. Keywords: bilateral, Critical Theory, East Asia, Korean Reunification, peace concepts